2006
DOI: 10.1016/j.foreco.2006.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-species plantations of Eucalyptus with nitrogen-fixing trees: A review

Abstract: Mixed-species plantations of Eucalyptus with a nitrogen (N 2 ) fixing species have the potential to increase productivity while maintaining soil fertility, compared to Eucalyptus monocultures. However, it is difficult to predict combinations of species and sites that will lead to these benefits. We review the processes and interactions occurring in mixed plantations, and the influence of species or site attributes, to aid the selection of successful combinations of species and sites. Successful mixtures, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

23
318
2
57

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 469 publications
(400 citation statements)
references
References 148 publications
(214 reference statements)
23
318
2
57
Order By: Relevance
“…The tolerance of eucalyptus to soil acidity and high Al contents, its adaptability to low soil fertility, and the ability to absorb N from different sources (Neves et al, 1990;Grespan et al, 1998) suggest that the use of this species in mixed plantations with N 2 -fixing leguminous trees could improve soil fertility and contribute to a more sustainable land use. Recent studies showed that intercropping eucalyptus with tree legumes was not detrimental to timber yield and resulted in increased soil N availability for eucalyptus (Binkley et al, 1992;Forrester et al, 2006). These results suggest that the implementation of such mixed forests may result in significant economical and ecological advantages due to the N input through biological nitrogen fixation (Forrester et al, 2006).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…The tolerance of eucalyptus to soil acidity and high Al contents, its adaptability to low soil fertility, and the ability to absorb N from different sources (Neves et al, 1990;Grespan et al, 1998) suggest that the use of this species in mixed plantations with N 2 -fixing leguminous trees could improve soil fertility and contribute to a more sustainable land use. Recent studies showed that intercropping eucalyptus with tree legumes was not detrimental to timber yield and resulted in increased soil N availability for eucalyptus (Binkley et al, 1992;Forrester et al, 2006). These results suggest that the implementation of such mixed forests may result in significant economical and ecological advantages due to the N input through biological nitrogen fixation (Forrester et al, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…Recent studies showed that intercropping eucalyptus with tree legumes was not detrimental to timber yield and resulted in increased soil N availability for eucalyptus (Binkley et al, 1992;Forrester et al, 2006). These results suggest that the implementation of such mixed forests may result in significant economical and ecological advantages due to the N input through biological nitrogen fixation (Forrester et al, 2006).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Size-asymmetric competition appears as the dominant structuring factor in both monoculture and mixed species plantations (Potvin and Dutilleul 2009) and only when these competitive effects are minimised, by matching species with compatible height growth and shade tolerances, can the positive interactions of facilitation and complementarity drive mixtures to out-yield monocultures (Forrester et al 2006). Competition for light is often asymmetrical between species, especially in mixtures that include rainforest trees with different shade tolerances .…”
mentioning
confidence: 99%